Postoperative Endodontic Pain after Treatment Using XP-endo Finisher: A Randomized Clinical Trial - Alexandre Fernandes, Leonardo; de Sousa Santos, Cristiane Flaviana; Portela Ditzel Westphalen, Vania; Xavier da Silva Neto, Ulisses; Carneiro, Everdan (Iranian Endodontic Journal, 2023)
Introduction: This randomized clinical trial aimed to determine whether the XP-endo finisher combined with or without foraminal enlargement has any significant effect on the incidence and intensity of postoperative pain in necrotic pulps. Materials and Methods: Clinical pain levels were measured after 6, 12, 24, 48, and 72 hours and at 7 postoperative days. All treatments were performed by an endodontist in a single visit. One hundred and twenty patients were included. All patients had a single tooth treated. The patients were divided into four groups: No FE (None Foraminal Enlargement) (n=30), FE (Foraminal Enlargement) (n=30), No FE+XPF (None Foraminal Enlargement+XP-endo Finisher) (n=30) and XPF+FE (XP-endo Finisher and Foraminal Enlargement) (n=30). The canals were irrigated with sodium hypochlorite, shaped using WaveOne Gold Medium file, and then filled by using a matching single cone and AH-Plus sealer. The cavity was filled using glass ionomer cement. Pain intensity was assessed using the visual analog scale. The data were analyzed with the ANOVA and Games-Howell test. The significance level was 5%. Results: The XPF+FE group experienced a higher level of pain, being classified on the visual analog scale as moderate for 48 postoperative hours and mild for 7 postoperative days (P<0.05). In the other groups, the pain was mild, only with different time intervals (P>0.05). Conclusions: Foraminal enlargement associated with XP-endo Finisher may cause moderate postoperative pain.